Creative females have larger white matter structures: Evidence from a large sample study. Issue 1 (20th September 2016) - Takeuchi, Hikaru; Taki, Yasuyuki; Nouchi, Rui; Yokoyama, Ryoichi; Kotozaki, Yuka; Nakagawa, Seishu; Sekiguchi, Atsushi; Iizuka, Kunio; Yamamoto, Yuki; Hanawa, Sugiko; Araki, Tsuyoshi; Makoto Miyauchi, Carlos; et al.
Abstract: The importance of brain connectivity for creativity has been theoretically suggested and empirically demonstrated. Studies have shown sex differences in creativity measured by divergent thinking (CMDT) as well as sex differences in the structural correlates of CMDT. However, the relationships between regional white matter volume (rWMV) and CMDT and associated sex differences have never been directly investigated. In addition, structural studies have shown poor replicability and inaccuracy of multiple comparisons over the whole brain. To address these issues, we used the data from a large sample of healthy young adults (776 males and 560 females; mean age: 20.8 years, SD = 0.8). We investigated the relationship between CMDT and WMV using the newest version of voxel‐based morphometry (VBM). We corrected for multiple comparisons over whole brain using the permutation‐based method, which is known to be quite accurate and robust. Significant positive correlations between rWMV and CMDT scores were observed in widespread areas below the neocortex specifically in females. These associations with CMDT were not observed in analyses of fractional anisotropy using diffusion tensor imaging. Using rigorous methods, our findings further supported the importance of brain connectivity for creativity as well as its female‐specific association. Hum Brain Mapp 38:414–430, 2017 . © 2016 Wiley Periodicals, Inc.